Changes to protocol in the regulation of adverse drug reactions – historical and current European view. (1st October 2016) - Mimica Matanović, Suzana
Abstract: Adverse drug reactions (ADRs) are an inevitable part of medication use. During clinical trials, limited information was gained on drug safety. After marketing authorization (MA), more safety data is available as more patients use the drug. Major changes in drug regulation came after drug disasters, like with sulphanilamide elixir or thalidomide use. In recent history, withdrawal of rofecoxib has demonstrated the importance of post-marketing safety monitoring. Subsequently, legislation on drug safety changed both in the United States (US) and in the European Union (EU), becoming simplified and more comprehensive. New EU legislation was implemented in 2012 and has broadened ADR definition to medication errors and overdoses. In the EU, the Pharmacovigilance Risk Assessment Committee (PRAC) has been formed within the European Medicines Agency (EMA), regulating all aspects of drug safety. Referral procedures enable a thorough scientific analysis on all issues of medication safety. In both the US and the EU, ADRs can be reported directly by patients. All reports of suspected ADRs are kept on electronic databases and are analyzed regularly using new technologies. New safety signals are subsequently discovered and evaluated. This author expects that the new regulations will effectively safeguard healthcare consumers from major drug risks.